2022
DOI: 10.1155/2022/3284313
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Color and Shape on Cognitive Performance

Abstract: Color and shape are important media for information perception, cognition, judgment, and decision making. However, the combined effects of color and shape on cognitive ability have not been widely investigated. In this paper, the perceptual load paradigm is used to investigate the combined effect on icon cognition. Thirty-four healthy subjects (17 males and 17 females, aged 20–26 years, mean = 24, and SD = 4.51) participated in three behavioral experiments using an in-subject design, in which response time and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Of course, the large number of medications clinicians find in the medication cart poses a challenge to a one-dimensional approach, but combining a few dimensions in medication containers' design features might assist clinicians during medication administration. [24][25][26][27][28][29]38 Above all, ensuring consistency of design features among manufacturers will guarantee that in case a hospital needs to replace their medication supplier, the design features of the medication the clinician will find in the medication cart will be the same. We are missing an opportunity to supplement human capabilities and give clinicians a safety feature that might be a barrier to the administration of the wrong medication.…”
Section: Solutions Designed To Fit the Human Capabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, the large number of medications clinicians find in the medication cart poses a challenge to a one-dimensional approach, but combining a few dimensions in medication containers' design features might assist clinicians during medication administration. [24][25][26][27][28][29]38 Above all, ensuring consistency of design features among manufacturers will guarantee that in case a hospital needs to replace their medication supplier, the design features of the medication the clinician will find in the medication cart will be the same. We are missing an opportunity to supplement human capabilities and give clinicians a safety feature that might be a barrier to the administration of the wrong medication.…”
Section: Solutions Designed To Fit the Human Capabilitiesmentioning
confidence: 99%
“…Most people can identify the shape of a Coca-Cola bottle or the pattern of a baseball or basketball. Of course, the large number of medications clinicians find in the medication cart poses a challenge to a one-dimensional approach, but combining a few dimensions in medication containers’ design features might assist clinicians during medication administration 24–29,38 …”
Section: Solutions Designed To Fit the Human Capabilitiesmentioning
confidence: 99%
“…Indeed, the use of dynamic visual stimuli, such as color motion, may engage attentional mechanisms and cognitive processing (50). Several studies have discussed the positive effects of colors on the brain (51)(52)(53), which may lead to improved postural balance in DT conditions without challenges. Additionally, previous studies have suggested that the effective use of color design in immersive digital contexts can positively influence an individual's cognitive performance and ID (54).…”
Section: Effect Of Visual Variability On Postural Balancementioning
confidence: 99%
“…Empirical studies generally streamline the environment and the task to influence cognitive load only in specific ways. For instance, adjusting time pressure is a commonly employed method [21,22]. Previous studies have investigated the effect of color on cognitive load under various conditions.…”
Section: Introductionmentioning
confidence: 99%